KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR MENGGUNAKAN VISUALISASI POSTER SEDERHANA - Fatimah Nurul Aufa; Imaniar Purbasari; Eko Widianto (WASIS : Jurnal Ilmiah Pendidikan, 2020)
This study aims to describe the improvement of students' speaking skills through simple poster media on the theme of my hero grade IV SDN 1 Loram Kulon Kudus. This research was conducted in class IV SDN 1 Loram Kulon with research subjects of 21 students. This research lasted for 2 cycles. Cycle 1, namely in sub-schemes 2 learning 1 and 3. Cycle 2 takes place in sub-schemes 2 in learning 4 and 6. Each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. This research shows that the use of poster media can improve speaking skills at SDN 1 Loram Kulon Kudus, this can be seen from the increase in cycle 1 to cycle 2 from 58% to 78% of the total 21 students.